Experimental and theoretical study of filtered optical feedback in a semiconductor laser - Fischer, A.P.A.; Andersen, O.K.; Yousefi, M.; Stolte, S.; Lenstra, D. (IEEE journal of quantum electronics, 2000)
We report on the systematical investigation of the steady-state regime and the dynamical behavior of a semiconductor laser subject to delayed filtered optical feedback. We study a Fabry-Perot (FP) interferometer type of filter placed in the external feedback loop of a diode laser. The effects of the filter on the locking of the diode laser frequency to the external cavity modes are described. We report and observe hysteresis, bistability, and multistability and show that all these are well described by a set of rate equations for the coupled laser and FP cavity system. We also present an experimental stability diagram that summarizes the dynamical behavior of the system.